Accuracy of Lelli Test in Diagnosing Anterior Cruciate Ligament Tear taking Arthroscopy as Gold Standard (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the accuracy of Lelli test in diagnosing anterior cruciate ligament tear taking arthroscopy as gold standard.Design: It was a cross-sectional survey.Place and Duration of Study: This study was conducted in the Department of Orthopedics, Sir Ganga Ram Hospital, Lahore from December 2015 to November 2016.Patients and Methods: 60 consecutive patients presenting in the outpatient department of Orthopedic Surgery Sir Ganga Ram Hospital, Lahore with suspected ACL tear were included in this study. Lelli test was performed in all these patients and the ACL tear was later confirmed upon arthroscopy which was taken as gold standard. A written informed consent was taken from every patient.Results: There were 52 male and 8 female patients in the study group with a male to female ratio of 6.5:1. The mean age was 28±6.1 years. ACL tear was suspected in 32 patients on a positive Lelli test while actual tear was confirmed in 34 patients on arthroscopy. When cross-tabulated, there were 31 true positive, 1 false positive, 3 false negative and 25 true negative cases on Lelli test. It yielded 91.18% sensitivity, 96.15% specificity and 93.33% accuracy with positive and negative predictive value of 96.88% and 89.29% respectively for Lelli test taking arthroscopy as gold standard.Conclusion: In the present study, Lelli test was found to be a reliable clinical test for diagnosing ACL tear with sensitivity and specificity superior to conventional clinical methods in current practice.
Keywords: Anterior Cruciate Ligament Tear, Lelli Test, Diagnostic Accuracy